Strategi Dinas Lingkungan Hidup terhadap Pengelolaan Sampah di Kabupaten Karimun - Siti Sarah Sihombing; Ardi Putra (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study aims to describe and analyze the strategies implemented by the Environmental Agency (DLH) of Karimun Regency in managing waste and to evaluate the effectiveness of these implementations in the field. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document reviews. Findings reveal that DLH Karimun has developed and executed key strategies, including the formulation of the Regional Waste Management Master Plan (RIPSD), optimization of Temporary Waste Disposal Sites (TPS) with 3R principles, active collaboration with waste banks and community groups, and community-based education and socialization efforts. However, operational challenges persist, particularly in waste transportation fleet distribution, handling of the Sememal Final Disposal Site (TPA), and monitoring and evaluation mechanisms that remain suboptimal. Additional challenges include limited human resources and funding, low public awareness, and regulatory conflicts impacting strategic decision-making. Nevertheless, the strategies implemented have contributed to improvements in environmental cleanliness across several sub-districts and increased volumes of processed waste through recycling initiatives. Community involvement through schools, youth organizations, family welfare groups, mutual cooperation activities, and waste banks proved critical to success. The study recommends the adoption of digital-based waste management systems (smart waste management), capacity building for DLH personnel, community empowerment, and revision of local regulations to support sustainable waste management. This will enhance the effectiveness and sustainability of DLH Karimun’s waste management strategies moving forward. The findings provide valuable insights for policy formulation and practical implementation in similar regional contexts.